Nurturing the Seeds of Change: Strengthening the Lifestyle Medicine Movement With the Donald A. Pegg Student Leadership Award - Jaini, Paresh A. (Am J Lifestyle Med, 2018)
Student-led Lifestyle Medicine Interest Groups (LMIGs) empower the next generation of healthcare professionals to tackle the pandemic of lifestyle-related chronic diseases and provide important pathways to increasing the visibility of Lifestyle Medicine (LM) in health professions schools. Each year, the Donald A. Pegg Student Leadership Award offers four allied health students a seed grant to start or support LMIGs at their schools as well as financial assistance to attend the annual American College of Lifestyle Medicine (ACLM) conference. The 2017 student winners were Paresh Jaini, Albert Barrera, Alyssa Greenwell, and Alicja Baska. With the support of the Pegg Award, the awardees and their faculty advisors have made great strides in LM at their institutions in the areas of research, community outreach, student education, and global networking. Their LMIG activities have included students presenting research at national conferences, initiating a chapter of the national organization Walk with a Doc, hosting educational lectures on LM principles, sponsoring plant-based cooking sessions, facilitating stress management workshops, and hosting a national-level LM congress in Europe. Through the ACLM, the Pegg Award generates an atmosphere of growth for LMIGs, fostering the expansion, vision, and integration of LM into the education of health professions students worldwide.